2022
DOI: 10.3390/cancers14215418
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of MicroRNAs as Non-Invasive Prostate Cancer Biomarkers: A Systematic Literature Review Based on a Machine Learning Approach

Abstract: Background: Prostate cancer (PCa) is the second leading cause of cancer-related deaths in men. Although the prostate-specific antigen (PSA) test is used in clinical practice for screening and/or early detection of PCa, it is not specific, thus resulting in high false-positive rates. MicroRNAs (miRs) provide an opportunity as biomarkers for diagnosis, prognosis, and recurrence of PCa. Because the size of the literature on it is increasing and often controversial, this study aims to consolidate the state-of-art … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 121 publications
(36 reference statements)
0
13
0
Order By: Relevance
“…Nevertheless, its role at different stages of cancer progression and how its expression changes during the multistep carcinogenesis, suggest that a second biomarker of known behaviour would be needed to better understand and gauge; hence the parallel definition of levels for miR-410-3p whose opposite behaviour under such conditions allows a double-check-point to finely tune accuracy of the molecular test. This strategy has been further confirmed by evidences that both biomarkers are reported detectable in studies from liquid biopsies such as urine, serum, plasma and whole blood reporting that the two tumour-derived miRNAs can enter the circulatory system and be measured in serum and plasma (16) . In this sense, different studies have supported that circulating miR-141-5p is significantly elevated in the sera of PC patients compared to healthy controls, being associated with more aggressive and advanced disease (high Gleason score and lymph node metastases).…”
Section: Introductionmentioning
confidence: 74%
See 2 more Smart Citations
“…Nevertheless, its role at different stages of cancer progression and how its expression changes during the multistep carcinogenesis, suggest that a second biomarker of known behaviour would be needed to better understand and gauge; hence the parallel definition of levels for miR-410-3p whose opposite behaviour under such conditions allows a double-check-point to finely tune accuracy of the molecular test. This strategy has been further confirmed by evidences that both biomarkers are reported detectable in studies from liquid biopsies such as urine, serum, plasma and whole blood reporting that the two tumour-derived miRNAs can enter the circulatory system and be measured in serum and plasma (16) . In this sense, different studies have supported that circulating miR-141-5p is significantly elevated in the sera of PC patients compared to healthy controls, being associated with more aggressive and advanced disease (high Gleason score and lymph node metastases).…”
Section: Introductionmentioning
confidence: 74%
“…In the context of PCa, the recent study of Zhang et al (1) has shown that the elevated expression of miR-410-3p -3p correlates with the downregulation of phosphatase and tensin-homolog on chromosome ten (PTEN) and results in an activation of the AKT/mTOR signaling pathway, showing that miR-410-3p -3p plays a crucial role as an oncogene in PTEN/AKT/mTOR pathway (11) . The parallel study of Liu et al (2) has provided further evidence that upregulation of miR-410-3p could promote a disease progression and a metastatic ability of PCa due to deactivation of PTEN protein, a natural inhibitor of PI3K/AKT/ mTOR as well as having similar significance in clear cell renal cell carcinoma (CCRCC) (12) . Furthermore, evidence of MiR-410-3p in PCa and CCRC cancers being expressed at a high has been provided thus supporting for both types of cancer (1, 2) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are released by cancer cells and detectable in all human biofluids, including plasma, serum, and urine. Many cancer-specific circulating miRNAs have been reported and are expected to serve as viable biomarkers for the early detection of various cancers [ 17 , 18 , 19 , 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…MiRNAs are 19 to 25 nucleotide-long endogenous molecules which are integral to regulating gene expression. Aberrant miRNA expression profiles have been described in several cancers and have been implicated as useful biomarkers which may aid cancer diagnostic and treatment [ 17 ]. In the current study, EVs obtained from OCC and normal ovaries in the same patients were compared to identify cancer-specific miRNAs in EVs released from OCC cells.…”
Section: Introductionmentioning
confidence: 99%